It is not all about BRCA: Cullin-Ring ubiquitin Ligases in ovarian cancer - Carlucci, A (Br J Cancer, 2015)
Mutations in the BRCA1 and BRCA2 genes predispose individuals to the development of breast and ovarian cancers. As a result, biochemical functions of BRCA1 and BRCA2 proteins are being characterised in great detail. These studies have prompted the use of PARP inhibitors to treat BRCA1 and BRCA2-deficient ovarian cancers. This example of synthetic lethality represents a conceptual progress made recently in the approach to cancer treatment and is being currently tested in multiple clinical trials. Other than BRCA1 and BRCA2, many other factors might influence the survival of ovarian cancer patients. Currently, ovarian cancer remains the fifth most common cancer in the United Kingdom among women. Recent evidence suggests benefit in the modulation of the ubiquitin-proteasome system for the treatment of ovarian cancer. In this manuscript, we review the role of Cullin-Ring ubiquitin Ligases (CRLs) in the pathogenesis of ovarian cancer and their potential therapeutic exploitation. CRLs comprise a large family of proteins that, like kinases, might represent ideal candidates for targeted therapy and provide a large repertoire for the development of new anti-cancer compounds.